PENGEMBANGAN BAHAN AJAR BERBASIS BUDAYA LOKAL KALIMANTAN BARAT UNTUK SISWA KELAS IV - Andriyani Heni Saputri; Hery Kresnadi; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The study aims to produce a development of teaching materials based on the local culture of Kalimantan Barat based resource worthy of use for IV grade of Sekolah Dasar Negeri 58 Sungai Raya Sub-District Kubu Raya Regency. The method used was research and development (RND) by adapting addie's model (analysis, design, development, development, completion). The source of this research data was observation and interview of students and teachers, assessments of products by materials experts and design experts and students' responses. The data collection techniques that were used are observation, interview, and questionnaires by material experts, design experts and student questionnaire responses. The results showed that during the process of developing teaching material based on the local culture of Kalimantan Barat had gone through 5 stages, namely analysis, design, development, implementation and evaluation. The feasibility of teaching materials based on the local culture of Kalimantan Barat has an average percentage of material aspects of 89% category was highly valid, an average design aspect of an 82% valid category. The limited trial of a highly valid category of 96% and a small group test of 5 days with an average percentage of 99% category was perfectly valid. Keywords: Development, Local Culture, Teaching Materials